'Snakes & Ladders': factors influencing access to appropriate care for children and young people with suspected juvenile idiopathic arthritis - a qualitative study - Tim Rapley; Carl May; Nicola Smith; Helen E. Foster (BMC, 2021)
Abstract Background Many children and young people with juvenile idiopathic arthritis (JIA) experience delay in diagnosis and access to right care. The reasons for delay are multi-factorial and influenced by patient and family, clinician and organisational factors. Our aim was to explore the experiences of care, from initial symptoms to initial referral to paediatric rheumatology. Methods We analysed one-to-one and joint qualitative interviews with families of children with JIA (n = 36) presenting to a regional paediatric rheumatology service in the UK. We interviewed 51 family members (including mothers, fathers, patients, grandmothers and an aunt) and 10 health professionals (including orthopaedic surgeons, paediatricians, paediatric immunologist, General Practitioner and nurse) and a teacher involved in the care pathway of these JIA patients. Interviews were audio-recorded and analysed according to the standard procedures of rigorous qualitative analysis - coding, constant comparison, memoing and deviant case analysis. Results The median age of the children was 6 years old (range 1-17), with a spread of JIA subtypes. The median reported time to first PRh MDT visit from symptom onset was 22 weeks (range 4-364 weeks). Three key factors emerged in the pathways to appropriate care: (i) the persistence of symptoms (e.g. 'change' such as limp or avoidance of previously enjoyed activities); (ii) the persistence of parents help-seeking actions (e.g. repeat visits to primary and hospital care with concern that their child is not 'normal'; iii) the experience and skills of health professionals resulting in different trajectories (e.g. no-real-concern-at-this-point or further-investigation-is-required). JIA was more likely to be considered amongst health practitioner if they had prior experiences of a child with JIA (moreso with a 'protracted pathway') or exposure to paediatric rheumatology in their training. Conversely JIA was more likely to be overlooked if the child had comorbidity such as learning disability or a chronic illness. Conclusions Care pathways are often 'turbulent' prior to a diagnosis of JIA with physical and emotional distress for families. There is need for greater awareness about JIA amongst health care professionals and observations of change (from family and non-health care professionals such as teachers) are key to trigger referral for paediatric rheumatology opinion.